(untitled) (American Journal of Islam and Society, 1993)
There is no question that contemporary western civilization has been dominant in the field of science since the Renaissance. Western scientific superiority is not limited to specific scientific disciplines, but is rather an ovetall scientific domination covering both the so-called exact and the human-social sciences. Western science is the primary reference for specialists in such ateas as physics, chemistry, biology, medicine, economics, psychology, and sociology. It is in this sense that Third World underdevelopment is not only economic, social, and industrial; it also suffers from scientific-cultutal underdevelopment, or what we call "The Other Underdevelopment" (Dhaouadi 1988). The imptessive progress of western science since Newton and Descartes does not meari, however, that it has everything tight or perfect. In fact, its flaws ate becoming mote visible. In the last few decades, western science has begun to experience a shift from what is called classical science to new science. Classical science was associated with the celestial mechanics of Copernicus, Kepler, Newton, the new physics of Galileo, and the philosophy of Descartes. Descartes introduced a radical division between mind and matter, while Newton and his fellows presented a new science that looked at the world as a kind of giant clock The laws of this world were time-reversible, for it was held that there was no difference between past and future. As the laws were deterministic, both the past and the future could be predicted once the present was known. The vision of the emerging new science tends to heal the division between matter and spirit and to do away with the mechanical dimension ...